Assessment of Water Quality of Blue Nile River in Sudan - Babiker Gurashi Abu Sabah, Rasha; Haroun Mohamed Adam, Abubaker; Mohamed Ali, Dawoud (Journal of Agronomy Research, 2018)
The objectives of this study were to quantify the fresh water quality of Blue Nile River before processing, identify the pollutants, and to determine the most polluted areas, and their impacts on living organisms as well as the surrounding environment. Thus, random water samples were collected and analyzed at the laboratory of the Ministry of Irrigation and Water Resources, Ground water and Wadis Directorates - Khartoum. The outcomes were compared with the World Health Organization standardization. The results revealed variations in the concentration of the studied elements taken from the different locations. But, the results indicated that the water quality is good, and it is within the permissible water use. However, further study is recommended to include seasonal variation as well as the biological analysis.
Keywords: Processing; pollution; standardization; Zones